2020
DOI: 10.5812/ijp.108095
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children and Neonates: A Comprehensive Review Article

Abstract: Context: Novel coronavirus (COVID-19) has become a new public health crisis, posing a great threat to the people all around the world. We aimed to review the articles on COVID-19 in pediatric population to help physicians and other healthcare workers understand the importance of detecting silent disease carriers in this age group and stop further transmission to other healthy individuals and manage symptomatic patients based on the latest recommendations. Methods: We searched databases including PubMed, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…There is a risk of infection and mortality in all age groups of children with COVID-19 infection [ 19 ]. From studies of Olivia et al in the United Kingdom, Philip et al in New York City, and the CDC, the severity and mortality of COVID-19 were higher in children under age 1 and adolescents [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a risk of infection and mortality in all age groups of children with COVID-19 infection [ 19 ]. From studies of Olivia et al in the United Kingdom, Philip et al in New York City, and the CDC, the severity and mortality of COVID-19 were higher in children under age 1 and adolescents [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms might be due to the differences in Angiotensin -converting enzyme 2 (ACE2) expression, innate immunity, and the influence of preventive strategies including closure of schools and day-care centers [20]. However, increased availability of PCR tests even for milder cases has played a great role in patient detection [1]. Li et al suggested that 86% of all early COVID-19 infections in China remained undiagnosed, while undocumented cases may have a lower transmission rate, their extensive number indicates that they could have been the origin of 79% of all early cases.…”
Section: Discussionmentioning
confidence: 99%
“…The novel coronavirus (COVID- 19) outbreak has evolved into a novel public health disaster, which the World Health Organization (WHO) has classified as a pandemic since March 11, 2020 [1]. However, the actual infection rates are probably similar to those of adults, even if the actual prevalence in children is difficult to quantify due to different symptoms, lack of consideration or less severe course of the disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Our case along with some other reported cases from all around the world [9] , [10] , [11] , [12] , seem to further support this route of transmission. Children and specially neonates with COVID-19 are mostly asymptomatic or develop mild symptoms for which supportive care usually suffices [13] , [14] , [15] . To date, our case seems to be the youngest survived patient among the very few neonatal cases who have received antiviral therapy (remdesivir), IVIG and corticosteroids due to respiratory failure and the critically unstable status resulting from COVID-19 [6] , [14] , [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%